2012
DOI: 10.2478/s11658-011-0031-y
|View full text |Cite
|
Sign up to set email alerts
|

p38 Mitogen-activated protein kinase modulates exocrine secretion in rabbit lacrimal gland

Abstract: Abstract:The lacrimal gland (LG) is an exocrine gland important for secretion of the tear film. The kinase p38 has important signal transduction functions, e.g. in gene transcription, but has previously not been known to modulate exocrine secretion. The aim of the current study was to investigate the role of p38 in carbachol (Cch)-induced LG secretion in LG acinar cells in vitro. Western blotting was used to determine the phosphorylation status of p38 and p42/44 and determine expression of p38 isoforms. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Thus, it might be worthwhile thinking whether a combination of hepatocytes and MSC might be the cell therapeutic of best choice. Indeed, there is evidence that the performance of hepatocytes is improved in co-culture with MSC (Ijima et al, 2008 ; Shi et al, 2009 ; Chen et al, 2012 ), and vice versa MSC differentiation into hepatocyte-like cells is promoted by inflammatory liver injury conditions (Dong et al, 2010 ; Li et al, 2010 ). Recent data even demonstrated that not MSC themselves but as yet unequivocally unidentified soluble factors secreted by MSC exert the beneficial effects on hepatocytes under ALF conditions in mice and rats (Parekkadan et al, 2007b ; van Poll et al, 2008 ; Zagoura et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be worthwhile thinking whether a combination of hepatocytes and MSC might be the cell therapeutic of best choice. Indeed, there is evidence that the performance of hepatocytes is improved in co-culture with MSC (Ijima et al, 2008 ; Shi et al, 2009 ; Chen et al, 2012 ), and vice versa MSC differentiation into hepatocyte-like cells is promoted by inflammatory liver injury conditions (Dong et al, 2010 ; Li et al, 2010 ). Recent data even demonstrated that not MSC themselves but as yet unequivocally unidentified soluble factors secreted by MSC exert the beneficial effects on hepatocytes under ALF conditions in mice and rats (Parekkadan et al, 2007b ; van Poll et al, 2008 ; Zagoura et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%